Study of UiTM faculty of pharmacy pharmacy students' perception on the influence of social networking towards their learning attitude - Zainal Abidin, Mariam (2015)
This research investigates the students' perception on the influence of social networking usage on their academic. The students' perception on social networking influence is important because it may can be used as one of the e-learning tool. Many students spends a lot of time per day on surfing social networking. From this research it is found that most UiTM pharmacy students (90%) spends more than 3 hours on sufing social networking. Based on finding alsothe primary purpose of surfing social networking among students is chatting (72%), posting photos(66%) which are categorized under entertainment purpose. Meanwhile, 62% used social media to communicate with the lecturer and class fellow. Besides that, there is significant relationship between time of surfing social networking per day and its effect on study timing (Pearson Chi-Square value=p<0.05). Based on students perception, students agree spendingmorc time on social media, will affect study timing. Furthermore, 75% students said social media change their study habits due to multi tasking. Because of this reasons, social networking might be useful to be used by lecturers as e-learning tool. Thus, this research also investigate the appropriateness of social networking as one of the e-learning tool. 84% agree that social networking can be apply as one of the e-leaming tool, only 16% felt social media not appropriate to be used.